Respuestas

2012-06-23T01:07:53+02:00

P(x) = mx^(a+b) +nx^(b+c) + rx^(c+d) + tx^(d+c) + qx^(c+3)

                                           _______    _______

                                                  se suman 


P(x) = mx^(a+b) +nx^(b+c) + (r+t)x^(c+d) + qx^(c+3)


ahora si podemos darle forma:


P(x) = mx^(a+b) +nx^(b+c) + (r+t)x^(c+d) + qx^(c+3)


P(x) = mx^(3) +nx^(2) + (r+t)x^(1) + qx^(0)


por que es completo y ordenado:


c+3=0      c+d=1        b+c=2       a+b=3   

c=-3       -3+d=1        b-3=2       a+5=3 

                  d=4        b=5          a=-2

 

un gusto.....=D